Proteases Underground: Analysis of the Maize Root Apoplast Identifies Organ Specific Papain-Like Cysteine Protease Activity - Schulze Hüynck, Jan; Kaschani, Farnusch; van der Linde, Karina; Ziemann, Sebastian; Müller, André N.; Colby, Thomas; Kaiser, Markus; Misas Villamil, Johana C.; Doehlemann, Gunther (Frontiers in Plant Science, 2019)
Plant proteases are key regulators of plant cell processes such as seed development, immune responses, senescence and programmed cell death (PCD). Apoplastic papain-like cysteine proteases (PLCPs) are hubs in plant-microbe interactions and play an important role during abiotic stresses. The apoplast is a crucial interface for the interaction between plant and microbes. So far, apoplastic maize PLCPs and their function have been mostly described for aerial parts. In this study, we focused on apoplastic PLCPs in the roots of maize plants. We have analyzed the phylogeny of maize PLCPs and investigated their protein abundance after salicylic acid treatment. Using activity-based protein profiling (ABPP) we have identified a novel root-specific PLCP belonging to the RD21-like subfamily, as well as three salicylic acid activated PLCPs. The root specific PLCP CP1C shares sequence and structural similarities to known CP1-like proteases. Biochemical analysis of recombinant CP1C revealed different substrate specificities and inhibitor affinities compared to the related proteases. This study characterized a root-specific PLCP and identifies differences between the SA-dependent activation of PLCPs in roots and leaves.